A Novel Fiber Collection System for Rotary Force Spinning Method - Dian Ahmad Hapidin; Elvina Ayu Ratnasari; Aan Priyanto; Khairurrijal Khairurrijal (Greensusmater, 2026)
Recent advancements in micro- to nano-scale fiber production, particularly through rotary force spinning (RFS), offer high production rates but face challenges in optimizing fiber collection efficiency. This study investigates the effect of spinneret angular speed on fiber collection performance of a novel RFS collector system. The collector system integrated zig-zag pole collectors with a rolling collector that seamlessly traverse between the poles for fiber assembly. This configuration enabled the produced fibers to be continuously assembled onto the rolling collector, thereby forming fibrous membranes directly during the spinning process. The collection performance was evaluated using polyvinylpyrrolidone (PVP) fibers fabricated at spinneret angular speeds ranging from 4000 to 11000 rpm. The results showed that the rolling collector captured up to 95.39% of the produced fibers at a high rotational speed of 11,000 rpm, whereas at lower rotational speed, most fibers were deposited onto the pole collectors, reaching 95.19% at 4000 rpm. These findings indicate that the proposed collector system effectively enhances fiber collection efficiency over a broad rotational speed range while enabling direct fibrous membrane formation in the RFS process.